Enhancing the EU Green Transition Through the Protection of Fundamental Rights in the Digital Environment .......... 193 - Sikora-Kalėda, Alicja; Kawka, Inga (Fundamental Rights and Climate Change: Exploring New Perspectives and Corresponding Remedies, 2025)
The European Union faces the dual challenge of advancing digital transformation while ensuring environmental protection and safeguarding fundamental rights. The article explores how EU legislation protecting fundamental rights including the GDPR, DSA, and AI Act, contribute to a human-centric digital transformation aligned with environment protection goal. It underscores the critical role of digital technologies in achieving ecological objectives, as outlined in EU policies like the Green Deal and Circular Economy Action Plan. By analyzing the application of environmental principles in the digital context, the article highlights the emergence of concepts like digital pollution and the potential need for a new right to a clean digital environment.